Penerapan Metode Median Clustering Untuk Clusterisasi Peternakan di Provinsi Maluku - M. Y. Matdoan; A. M. Balami; F. Kondolembang; S. J. Latupeirissa (Hasanuddin University, 2023)
Livestock in Maluku Province is one of the sectors that is the main priority in the context of increasing people's welfare. The potential for livestock in Maluku Province is increasing every year. However, there needs to be integrated processing and identification of potential commodities in each region. One method that is a reliable statistical method is to use the median clustering method. Median clustering is a method of grouping based on the median value. The median clustering algorithm selects K cluster centers with the aim of minimizing the sum of the measurement distances between each point cluster and the closest cluster center. The data used in this study came from the Maluku Province Central Bureau of Statistics (BPS) in 2022. The results of this research were that there were 3 clusters formed in livestock clusterization in regencies and cities in Maluku Province. Clus ter 1 consists of Southwest Maluku Regency. Cluster 2 consists of the Regencies of Central Maluku, Buru and West Seram. Furthermore, Cluster 3 consists of the Tanimbar Islands, Southeast Maluku, Aru Islands, Eastern Seram, South Buru, Ambon and Tual City.